2010
DOI: 10.2298/tsci1001073m
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and heat transfer effects on exponentially accelerated vertical plate with variable temperature

Abstract: An exact solution of unsteady flow past an exponentially accelerated infinite vertical plate with variable temperature has been presented in the presence of uniform mass diffusion. The plate temperature is raised linearly with time and species concentration level near the plate is made to rise Cw. The dimensionless governing equations are solved using Laplace-transform technique. The velocity profiles fields are studied for different physical parameters like thermal Grashof number, mass Grashof number, Schmidt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Muthucumaraswamy et al [4] studied the flow past an exponentially accelerated infinite vertical plate in the presence of variable surface temperature. Again Muthucumaraswamy et al [5] analysed the combined effects of heat and mass transfer on exponentially accelerated vertical plate in presence of uniform magnetic field. Rajesh et al [6] presented the analytic investigation of radiation and mass transfer effects on MHD free convection flow past an exponentially accelerated vertical plate in the presence of variable mass diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Muthucumaraswamy et al [4] studied the flow past an exponentially accelerated infinite vertical plate in the presence of variable surface temperature. Again Muthucumaraswamy et al [5] analysed the combined effects of heat and mass transfer on exponentially accelerated vertical plate in presence of uniform magnetic field. Rajesh et al [6] presented the analytic investigation of radiation and mass transfer effects on MHD free convection flow past an exponentially accelerated vertical plate in the presence of variable mass diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Saha et al [13] investigated various ranges of Richardson number for combined free and forced convection inside a two-dimensional multiple ventilated rectangular enclosure. The unsteady flow past a uniformly accelerated infinite vertical plate in the presence of variable temperature and mass flux was proposed by Muthucumaraswamy et al [9]. The results indicated that the velocity increased with increasing values of thermal Grashof number or mass Grashof number.…”
Section: Introductionmentioning
confidence: 90%
“…First, for u -momentum in (9), by using central difference around ( ) 1 2, i j + the equation becomes…”
Section: Discretization Of Momentum and Continuity Equationsmentioning
confidence: 99%
See 1 more Smart Citation